Cardioprotection in cancer therapy: novel insights with anthracyclines. Issue 5 (6th February 2019) - Raber, Inbar; Asnani, Aarti
Abstract: Anthracyclines are a class of antineoplastic agents that remain critical to modern-day cancer treatment. However, their propensity to cause cardiotoxic effects limits their use and can cause increased morbidity and mortality among patients with cancer. Currently available methods to minimize the impact of anthracycline cardiotoxicity have not been widely successful. While it is largely accepted that the generation of oxygen radicals contributes to the development of anthracycline cardiotoxicity, the exact mechanisms of cardiomyocyte injury remain unclear. In this review, we discuss the current state of basic and translational research on the cardiotoxic mechanisms of anthracyclines that have led to the discovery of new therapeutic targets. Pending validation in patient populations, these recent advances have the potential to be translated into clinical approaches that will minimize anthracycline cardiotoxicity and improve outcomes in cancer survivors.